Steel Wire Wrapped Bamboo – As a Sustainable Reinforcement in Alkali Activated Fly Ash-Slag based Concrete (Global Journals of Research in Engineering, 2022)
The cost ratio of steel to concrete exceeding 100 in most of the RCC structures alternative materials for replacing steel are underway to develop a sustainable built environment Bamboo has been in housing industry since time memorial as a standalone structural member for lighter loads of roofing and wall cladding units It has been tested for its use as reinforcement in OPC based cement concrete structures replacing steel reinforcement with appreciable performance while requiring serious attention on serviceability and durational aspects The alkali activated low calcium fly ash slag-based concrete with steel reinforcement as structural components cured at ambient temperature RGPC are being popularized in the most consumed sector of concrete construction industry The present research work outlines the efficacy of binding wire wrapped bamboo splints as reinforcement along with bamboo fibers in alkali activated geopolymer concrete GPC The flexural behavior of Steel wire wrapped bamboo splints SWBS as reinforcement in GPC beams provide valuable feedback on the use of bamboo as reinforcement and fiber
Keywords: bamboo; geopolymer concrete; flexural behavior; fly ash; GGBS alkaline solution; crack width